Scientific and Social Relevance: A perspective study of six European nation’s reports to the development of educational research and educational science - Hofstetter, Rita; Schneuwly , Bernard (Swiss Journal of Educational Research, 2000)
What informs and directs the development of educational research and educational science? This contribution examines, in particular, the effects of a nation’s social requirements on the development of their educational research. Synthesized from pre-existing analyses, the first part works out a theoretical foundation for a description of the process of the «disciplinarisation» of educational science. In the second part, the content of the educational research of the selected six national reports (Germany, France, the Netherlands, Portugal, Sweden, and Switzerland), which were authorized by official agencies, is analyzed. With its intent predominantly heuristic, the paper shows how the social requirements function as regulatory mechanisms and how their influences on the development of educational research are perceived and described. The analysis concludes with a description and discussion of contrasting configurations of educational research based on a reading of the reports, and culminates in a series of theoretical and empirical questions that encourage follow-up research.